Faktor-Faktor yang Mempengaruhi Harga Saham di Bursa Efek Indonesia pada Perusahaan Trade Service and Investment - Eko Darmawan Suwandi; Akhmad Syarifudin (Owner : Riset dan Jurnal Akuntansi, 2023)
Fundamental analysis is an analysis method by looking at the company's financial statements to determine whether the stock to be chosen is a good stock in the future. Financial statements are records of financial information of a company in a certain accounting period that can be used to describe the company's performance or the condition of the company. One of the components in a company's financial statements is EPS, ROA, and ROE. This study aims to determine the effect of EPS (Earnings per Share), ROA (Return on Assets), and ROE (Return on Equity) on stock prices. The population used in this study are Trade Service And Investment companies that are listed on the Indonesia Stock Exchange for 2017 – 2021. The data used is secondary data by taking the sample using a purposive sampling technique, namely how to select a sample based on predetermined criteria and obtain a sample In this research, there were 14 companies during the 2017-2021 period. Methods of data analysis in the form of descriptive analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing. The research results show that EPS (Earnings per Share) has a positive and significant effect on stock prices. ROA (Return on Assets) has a positive and significant effect on stock prices, and ROE (Return on Equity) also has a positive and significant effect on stock prices.